ANALISIS PERIODE ULANG HUJAN MAKSIMUM DENGAN BERBAGAI METODE(RETURN PERIOD ANALYZE MAXIMUM RAINFALL WITH THREE METHOD) - . Basuki; Iis Winarsih; Noor Laily Adhyani (Agromet, 2009)
Lush rainfall intensity in Indonesia mostly often affecting to flood disaster. Managing in flood problem must be supporting by good infrastructure of flood management such as dam, irrigation system, drainages,etc. In designing a water building, we needs maximum rainfall information with certain return period. The amount of maximum rainfall for design are different according to lifetime and reservoir capacity such as for a big dam that needs maximum rainfall information with long return period approximately 50,100 years, and for irrigation system needs shorter maximum rainfall information about 2,5,10 years. We use three methods in this analysis: E.J. Gumbel Method, Log Pearson III Method and Iway Kadoya Method. Result of analysis from above methods show that Log Pearson III method and Iway Kadoya method as identically as E.J Gumbell method.